Draft Genome Sequences of Two Sporothrix schenckii Clinical Isolates Associated with Human Sporotrichosis in Colombia (2018)
ABSTRACT: Sporothrix schenckii is a thermodimorphic fungal pathogen with a high genetic diversity. In this work, we present the assembly and similarity analysis of the whole-genome sequences of two clinical isolates from Colombia of S. schenckii sensu stricto.